Effectiveness of vaccination against COVID-19 in reducing lethality in infected patients - Romero-Robles, Milton A. (2025)
The objective of this study was to estimate vaccine effectiveness against SARS-CoV-2 in reducing mortality from COVID-19 among adults with partial, complete, and booster immunization compared to unvaccinated individuals. A retrospective cohort study was conducted, including adults treated within the Ancash – EsSalud healthcare network (Peru) between January and March 2022, with infection confirmed by RT-PCR and/or antigen tests. Data from NOTICOVID and SINADEF were utilized. Crude (HRc) and adjusted hazard ratios (HRa) were calculated to assess the association between immunization status and COVID-19 mortality. Vaccine effectiveness (VE) was computed as VE% = (1 – HR)*100. A total of 972 adults (52.9% female) with a median age of 42 years were analyzed; 9.4% had comorbidities. Booster immunization demonstrated a significantly lower hazard of death compared to unvaccinated individuals (HRa: 0.06; 95% CI: 0.02–0.23). Booster vaccination is concluded as a critical strategy to reduce COVID-19 mortality and to strengthen public immunization policies.